1981
DOI: 10.1083/jcb.89.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Lectin labeling of sprouting neurons. II. Relative movement and appearance of glycoconjugates during plasmalemmal expansion.

Abstract: To study the dynamics of membrane components during neuritic growth, we carried out a series of pulse-chase experiments with ferritin-conjugated and unconjugated lectins on sympathetic neurons sprouting in vitro. Labeling of aldehyde-prefixed cultures with wheatgerm agglutinin or with the galactose-specific lectin of Ricinus communis is consistently dense near the distal end of the neurites . By contrast, if live cultures are labeled with these lectins and chased for 3-20 min, label-free plasmalemmal areas app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 40 publications
5
65
0
Order By: Relevance
“…114,116 The activation of this pathway in hippocampal cells induced membrane assembly at the axonal growth cone, a key parameter of axonal growth. [126][127][128][129][130] Whereas in PC12 cells the PI3/Akt signaling mechanism was accompanied by an increase in neurofilament protein NF68 a marker of neuronal differentiation. 114,131,132 Three studies done with PC12 cells 114,115,117 and one done with hippocampal cells 116 found that Akt activation was followed by GSK-3 phosphorylation which as a result can lead to microtubule polymerization 112 and consequently, neurite formation.…”
Section: Akt1mentioning
confidence: 99%
“…114,116 The activation of this pathway in hippocampal cells induced membrane assembly at the axonal growth cone, a key parameter of axonal growth. [126][127][128][129][130] Whereas in PC12 cells the PI3/Akt signaling mechanism was accompanied by an increase in neurofilament protein NF68 a marker of neuronal differentiation. 114,131,132 Three studies done with PC12 cells 114,115,117 and one done with hippocampal cells 116 found that Akt activation was followed by GSK-3 phosphorylation which as a result can lead to microtubule polymerization 112 and consequently, neurite formation.…”
Section: Akt1mentioning
confidence: 99%
“…The Ca2+-dependent membrane fusion in growth cones has been studied by the Phenninger's group, though proteins involved in the fusion have not been identified. They have developed a cell-free membrane expansion assay using intact growth cone particles and found that high potassium depolarization and calcium-ionophore treatment cause significant increases in exposed WGA binding sites within minutes [22,23]. By morphometric analysis, the source of the newly added plasma membranes has been identified as clear vesicles (150 nm in diameter).…”
Section: Discussionmentioning
confidence: 99%
“…The source of the membrane for the rapidly growing axolemma and the mode by which the membrane is added to the axolemma have been of primary interest. Pfeninger et al have demonstrated in vitro that some clear vesicles localized in growth cones fuse with the axolemma in a Cat-dependent manner [22,23]. The molecules involved in the Cat-dependent membrane fusion in the growth cones are, however, largely unknown.…”
mentioning
confidence: 99%
“…Prolonged exposure to lectin at 36°C is expected to lead to a decrease in the density of binding sites because of internalization and/or capping-like rearrangement ofthe membrane-bound ligand. The observed decrease in binding sites (20).…”
Section: Cell Surface Contaminationmentioning
confidence: 99%
“…Thus, cellular polarity is also reflected in cell surface chemistry . This finding has to be viewed in light of the fact that neuronal plasmalemma is expanding very rapidly during neuritic growth, and that addition of certain new components to the plasma membrane occurs predominantly in the growth cone area, whereas other membrane components appear to be added primarily at the perikaryon (19,20,22 Labeling of spinal cord anterior horn neurons with F-RCA II and F-SBA. All samples were aldehyde-fixed before labeling .…”
Section: Region-specific Membrane Composition In the Growing Neuronmentioning
confidence: 99%